Low Temperature Biodisinfection Effectiveness for Phytophthora capsici Control of Protected Sweet Pepper Crops in the Southeast of Spain - Guerrero, María del Mar; Lacasa, Carmen Mª; Martínez, Victoriano; Martínez, Mª Carmen; Monserrat, Antonio; Larregla, Santiago (Frontiers in Sustainable Food Systems, 2021)
Biodisinfection using fresh sheep manure in August is effective in controlling Phytophthora root rot in greenhouses in southeast Spain, but this is not the case after the beginning of September. The effectiveness of biodisinfection of new amendments has been evaluated beginning in October in sweet pepper greenhouses to control Phytophthora capsici. The amendments used were: T1: wheat husk + fresh sheep manure (FSM), 3.5 kg m−2; T2: sunflower pellets 3.5 kg m−2; T3: FSM: 3.5 kg m−2; T4: Control. Temperatures above 40°C were obtained in some amendments; anoxic conditions were found in all amendments, and also a reduction of the viability of P. capsici oospores with respect to the control, as well as a higher yield. The contribution of fresh sheep manure to the amendments did not lead to an improvement in their effectiveness. Autumn biodisinfection under low temperature conditions using fresh organic amendments that enhance soil anaerobic conditions may be a promising strategy for the control of P. capsici in pepper greenhouses in southeastern Spain.